The impact of systemic racism on health outcomes among Black women: Recommendations for change. Issue 2 (February 2023) - James-Conterelli, Sascha; Dunkley, Daihnia; McIntosh, Jennifer T.; Julien, Tamika; Nelson, Maurice D.; Richard-Eaglin, Angela
Abstract: Black women suffer disproportionately from healthcare inequities in comparison to their White counterparts. Using the Public Health Critical Race framework, this article explores the lasting effects of systemic racism on the health outcomes of Black women across the lifespan. A case study and specific strategies are presented to examine how clinicians, educators, and policymakers can work with Black women to mitigate and eliminate health inequities. Abstract : Black women suffer disproportionately from healthcare inequities in comparison to their White counterparts. Using the Public Health Critical Race framework, this article explores the lasting effects of systemic racism on the health outcomes of Black women across the lifespan. A case study and specific strategies are presented to examine how clinicians, educators, and policymakers can work with Black women to mitigate and eliminate health inequities.